2020
DOI: 10.18203/2349-3291.ijcp20200211
|View full text |Cite
|
Sign up to set email alerts
|

Association of cord blood and maternal lipid profile

Abstract: Background: Cardiovascular diseases (CVDs) are the leading cause of mortality and morbidity with dyslipidemia as an important contributing risk factor. Objective of the study was to determine whether there is an association between maternal lipid profile and the cord blood lipid profile of their newborns.Methods: This was a hospital-based Cross-sectional study on 60 mothers and their respective newborns (30 term and 30 preterm) conducted in Yenepoya medical college hospital from August to November 2019. Umbili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…The high TGL in these studies has been partly attributed to a high prevalence of vitamin D deficiency (9,10). The values of HDL and LDL in our study were like the reported values by other studies (5,16). The characteristics of the child including sex, BMI, head circumference does not seem to influence the cord blood lipid profile.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The high TGL in these studies has been partly attributed to a high prevalence of vitamin D deficiency (9,10). The values of HDL and LDL in our study were like the reported values by other studies (5,16). The characteristics of the child including sex, BMI, head circumference does not seem to influence the cord blood lipid profile.…”
Section: Discussionsupporting
confidence: 89%
“…In our study the mean TC was 73.31mg%, like those reported by other studies from India (5,14) (8), higher TGL levels were reported in Iranian newborns (9,10). The high TGL in these studies has been partly attributed to a high prevalence of vitamin D deficiency (9,10).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation